L' utopia di Adriano Olivetti: La profezia dell'integralità nella fabbrica-comunità - Clemenza, Antonino (Antonianum, 2022)
The experience and the thought of Adriano Olivetti have been imprinted on the history of entrepreneurship, not only in Italy but also internationally. His transdisciplinary thought, in its organic vision of the factory (as) community, was prophetic, a realised and propositive utopia, which sets up an inviting challenge for today. His "factories of the good" were places of education in "incarnated" values, even as meaningful political communities, set to create value, beginning with care for the integral human being.